A positive electrode sheet for sodium ion battery and a preparation method thereof, and a sodium ion battery
By setting the first partition coating to isolate from aluminum foil and the second partition coating to isolate from air in the positive electrode sheet of the sodium ion battery, the problem of reacting sodium oxide or sodium hydroxide with the material in the positive electrode sheet is solved, and the battery performance and stability are improved sex.
Patent Information
- Application Number
- CN202211200924.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-09-29
AI Technical Summary
The sodium oxide or sodium hydroxide in the positive electrode sheet of the sodium ion battery reacts with the moisture and carbon dioxide in the aluminum foil or air to form sodium carbonate or sodium bicarbonate, affecting the performance of the positive electrode sheet.
A first partition coating is provided between the positive electrode current collector and the positive electrode active coating to avoid reaction of sodium oxide or sodium hydroxide and aluminum foil; a second partition coating is provided on the outermost side of the positive electrode active coating to avoid sodium oxide or sodium hydroxide. React with moisture or carbon dioxide in the air.
The reaction is effectively avoided to produce sodium carbonate or sodium bicarbonate, reduce the influence of air on the positive electrode active material layer, and improve the performance and stability of the positive electrode sheet.
Smart Images

Figure CN115498140B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a positive electrode sheet for a sodium ion battery and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the excessive demand for lithium resources in the large-scale application of lithium-ion batteries, it is bound to face the problem of shortage. At the same time, due to the crazy rise in the price of raw materials for lithium resources, the manufacturing cost of lithium batteries continues to increase.
[0003] In recent years, with the rapid development of battery technology, sodium-ion batteries have been launched one after another. Their working principles are the same as those of lithium-ion batteries. Their notable features are low cost, abundant resources, and no use of expensive rare metals such as lithium and cobalt. Therefore, they have received widespread attention.
[0004] The biggest difference between sodium-ion batteries and lithium-ion batteries is that their positive and negative electrode materials are different. The positive electrode materials of sodium-ion batteries generally include layered oxides, Prussian blue compounds, and polyanion types. The positive electrode materials of sodium-ion batteries generally contain a small amount of sodium oxide or sodium hydroxide. Since the foil used for the positive electrode is aluminum foil, there is a certain reaction of the aluminum foil to a certain extent. At the same time, due to the presence of sodium hydroxide, it will also react with moisture and carbon dioxide in the air. In order to avoid or slow down the reaction of the foil to generate sodium carbonate or sodium bicarbonate, new requirements are put forward for the positive electrode sheet processing technology of sodium-ion batteries. Therefore, it is very necessary to provide an electrode structure and processing method. Summary of the invention
[0005] One of the purposes of the present invention is to provide a positive electrode sheet for a sodium ion battery in view of the deficiencies of the prior art, wherein a first separator coating is provided between the positive electrode current collector and the positive electrode active coating to prevent the sodium oxide or sodium hydroxide contained in the positive electrode active coating from reacting with the aluminum foil, and a second separator coating is provided on the outermost side of the positive electrode active coating to prevent the sodium oxide or sodium hydroxide contained in the positive electrode active coating from reacting with moisture or carbon dioxide in the air to avoid the reaction to generate sodium carbonate or sodium bicarbonate, thereby reducing the influence of air on the positive electrode active material layer.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention comprises a positive electrode current collector, a first separation coating arranged on at least one surface of the positive electrode current collector, a positive electrode active coating arranged on the side of the functional coating away from the positive electrode current collector, and a second separation coating arranged on the surface of the positive electrode active coating.
[0008] Preferably, the first separation coating layer comprises the following raw materials in parts by weight: 50 to 80 parts of carboxyvinyl poly, 10 to 30 parts of lithium hydroxide, 10 to 30 parts of boehmite and 2 to 10 parts of a conductive agent.
[0009] Preferably, the porosity of the first separation coating layer is 30% to 60%.
[0010] Preferably, the thickness of the first separation coating layer is 0.2-10 μm.
[0011] Preferably, the second separation coating layer comprises the following raw materials in parts by weight: 50 to 80 parts of carboxyvinyl poly, 10 to 30 parts of lithium hydroxide, 10 to 30 parts of boehmite and 2 to 10 parts of a conductive agent.
[0012] Preferably, the porosity of the second separation coating layer is 30% to 60%.
[0013] Preferably, the second separation coating has a thickness of 0.2-10 μm.
[0014] The second object of the present invention is to provide a method for preparing a positive electrode sheet for a sodium ion battery in view of the deficiencies of the prior art, which has simple preparation, good controllability and can be mass-produced.
[0015] In order to achieve the above object, the present invention adopts the following technical solutions:
[0016] A method for preparing a positive electrode sheet for a sodium ion battery comprises the following steps:
[0017] Step S1, adding carboxyvinyl polyol into a solvent and stirring to obtain carboxyvinyl polyol slurry;
[0018] Step S2, adding lithium hydroxide to a solvent, stirring, and sealing to obtain a lithium hydroxide solution;
[0019] Step S3, adding boehmite and a conductive agent to the carboxyvinyl polyslurry and stirring in vacuum, adding lithium hydroxide solution and a solvent, and stirring in vacuum for a second time to obtain a separator coating slurry;
[0020] Step S4, coating the separator coating slurry on the surface of the aluminum foil, drying to obtain a first separator coating, coating the positive electrode active slurry on the surface of the first separator coating, drying to obtain a positive electrode active coating, coating the separator coating slurry on the surface of the positive electrode active coating, drying to obtain a second separator coating, and preparing a positive electrode sheet for a sodium ion battery.
[0021] Preferably, the vacuum degree of the vacuum stirring in step S3 is ≤-30KPa, the stirring speed is 10-30rpm / min, and the stirring time is 20-50 minutes. The vacuum degree of the secondary vacuum stirring is ≤-90KPa, the stirring speed is 10-30rpm / min, and the stirring time is 20-50 minutes.
[0022] The second object of the present invention is to provide a sodium ion battery with lower internal resistance and good cycle performance in view of the deficiencies in the prior art.
[0023] In order to achieve the above object, the present invention adopts the following technical solutions:
[0024] A sodium ion battery comprises the above-mentioned positive electrode sheet for a sodium ion battery.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: a positive electrode sheet for a sodium ion battery of the present invention is provided with a first separator coating between the positive electrode current collector and the positive electrode active coating to prevent the sodium oxide or sodium hydroxide contained in the positive electrode active coating from reacting with the aluminum foil, and a second separator coating is provided on the outermost side of the positive electrode active coating to prevent the sodium oxide or sodium hydroxide contained in the positive electrode active coating from reacting with moisture or carbon dioxide in the air, to avoid the reaction to generate sodium carbonate or sodium bicarbonate, and to reduce the influence of air on the positive electrode active material layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic structural diagram of a positive electrode sheet for a sodium ion battery of the present invention.
[0027] Among them: 1. positive electrode current collector; 2. first separation coating; 3. positive electrode active coating; 4. second separation coating. DETAILED DESCRIPTION
[0028] The present invention will be described in further detail below in conjunction with specific implementation modes and the accompanying drawings, but the implementation modes of the present invention are not limited thereto.
[0029] A positive electrode sheet for a sodium ion battery comprises a positive electrode current collector 1, a first separation coating 2 arranged on at least one surface of the positive electrode current collector 1, a positive electrode active coating 3 arranged on a side of the functional coating away from the positive electrode current collector 1, and a second separation coating 4 arranged on the surface of the positive electrode active coating 3.
[0030] The positive electrode active coating 3 generally contains residual sodium oxide, sodium hydroxide, water, etc., which are easy to react with the aluminum foil of the positive electrode current collector 1 to produce sodium aluminate and then corrode the aluminum foil. In addition, carbon dioxide and water in the air will also react with the sodium oxide or sodium hydroxide in the positive electrode active coating 3 to generate sodium carbonate or sodium bicarbonate, affecting the performance of the positive electrode active coating 3. In a positive electrode sheet for a sodium ion battery of the present invention, a first separator coating 2 is arranged between the positive electrode current collector 1 and the positive electrode active coating 3 to prevent the sodium oxide or sodium hydroxide contained in the positive electrode active coating 3 from reacting with the aluminum foil, and a second separator coating 4 is arranged on the outermost side of the positive electrode active coating 3 to prevent the active material in the positive electrode active coating 3 from reacting with water or carbon dioxide in the air, reduce the influence of air on the positive electrode active material layer, and ensure the performance quality of the positive electrode sheet.
[0031] In some embodiments, the first separation coating 2 comprises the following raw materials in parts by weight: 50-80 parts of carboxyvinyl poly, 10-30 parts of lithium hydroxide, 10-30 parts of boehmite and 2-10 parts of conductive agent. Preferably, the first separation coating 2 comprises the following raw materials in parts by weight: 50-55 parts of carboxyvinyl poly, 10-20 parts of lithium hydroxide, 10-20 parts of boehmite and 2-6 parts of conductive agent; 55-58 parts of carboxyvinyl poly, 20-30 parts of lithium hydroxide, 20-30 parts of boehmite and 6-10 parts of conductive agent; 60-80 parts of carboxyvinyl poly, 25-30 parts of lithium hydroxide, 25-30 parts of boehmite and 6-10 parts of conductive agent; specifically, the first separation coating 2 The invention comprises the following raw materials in parts by weight: 50 parts of carboxyvinyl poly, 10 parts of lithium hydroxide, 10 parts of boehmite, and 2 parts of conductive agent; 54 parts of carboxyvinyl poly, 13 parts of lithium hydroxide, 14 parts of boehmite, and 4 parts of conductive agent; 57 parts of carboxyvinyl poly, 16 parts of lithium hydroxide, 23 parts of boehmite, and 6 parts of conductive agent; 60 parts of carboxyvinyl poly, 24 parts of lithium hydroxide, 30 parts of boehmite, and 8 parts of conductive agent; 80 parts of carboxyvinyl poly, 24 parts of lithium hydroxide, 30 parts of boehmite, and 8 parts of conductive agent.
[0032] In some embodiments, the porosity of the first separation coating 2 is 30% to 60%, the porosity of the first separation coating 2 is 30%, 35%, 40%, 45%, 50%, 55%, 60%.
[0033] In some embodiments, the thickness of the first separation coating 2 is 0.2-10 μm. The thickness of the first separation coating 2 is 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 3 μm, 5 μm, 7 μm, 7.5 μm, 10 μm.
[0034] In some embodiments, the second separation coating 4 comprises the following raw materials in parts by weight: 50-80 parts of carboxyvinyl poly, 10-30 parts of lithium hydroxide, 10-30 parts of boehmite and 2-10 parts of conductive agent. Preferably, the second separation coating 4 comprises the following raw materials in parts by weight: 50-55 parts of carboxyvinyl poly, 10-20 parts of lithium hydroxide, 10-20 parts of boehmite and 2-6 parts of conductive agent; 55-58 parts of carboxyvinyl poly, 20-30 parts of lithium hydroxide, 20-30 parts of boehmite and 6-10 parts of conductive agent; 56-60 parts of carboxyvinyl poly, 25-30 parts of lithium hydroxide, 25-30 parts of boehmite and 6-10 parts of conductive agent; 60-80 parts of carboxyvinyl poly, 25-30 parts of lithium hydroxide, 25-30 parts of boehmite and 6-10 parts of conductive agent. Specifically, the second separation coating 4 comprises the following raw materials in parts by weight: 50-55 parts of carboxyvinyl poly, 10-20 parts of lithium hydroxide, 10-20 parts of boehmite and 2-6 parts of conductive agent; 55-58 parts of carboxyvinyl poly, 20-30 parts of lithium hydroxide, 20-30 parts of boehmite and 6-10 parts of conductive agent; The separation coating 4 includes the following raw materials in parts by weight: 50 parts of carboxyvinyl poly, 10 parts of lithium hydroxide, 10 parts of boehmite, and 2 parts of conductive agent; 54 parts of carboxyvinyl poly, 13 parts of lithium hydroxide, 14 parts of boehmite, and 4 parts of conductive agent; 57 parts of carboxyvinyl poly, 16 parts of lithium hydroxide, 23 parts of boehmite, and 6 parts of conductive agent; 60 parts of carboxyvinyl poly, 24 parts of lithium hydroxide, 30 parts of boehmite, and 8 parts of conductive agent; 70 parts of carboxyvinyl poly, 24 parts of lithium hydroxide, 30 parts of boehmite, and 8 parts of conductive agent; 80 parts of carboxyvinyl poly, 24 parts of lithium hydroxide, 30 parts of boehmite, and 8 parts of conductive agent.
[0035] In some embodiments, the porosity of the second separation coating 4 is 30% to 60%, the porosity of the second separation coating 4 is 30%, 35%, 40%, 45%, 50%, 55%, 60%.
[0036] In some embodiments, the thickness of the second separation coating 4 is 0.2-10 μm. The thickness of the second separation coating 4 is 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 4 μm, 6 μm, 8 μm, or 10 μm.
[0037] A method for preparing a positive electrode sheet for a sodium ion battery comprises the following steps:
[0038] Step S1, adding carboxyvinyl polyol into a solvent and stirring to obtain carboxyvinyl polyol slurry;
[0039] Step S2, adding lithium hydroxide to a solvent, stirring, and sealing to obtain a lithium hydroxide solution;
[0040] Step S3, adding boehmite and a conductive agent to the polycarboxyvinyl slurry and stirring the mixture in vacuum, adding a lithium hydroxide solution and a solvent, and stirring the mixture in vacuum for a second time to obtain a separator coating slurry;
[0041] Step S4, coating the separator coating slurry on the surface of the aluminum foil, drying to obtain the first separator coating 2, coating the positive electrode active slurry on the surface of the first separator coating 2, drying to obtain the positive electrode active coating 3, coating the separator coating slurry on the surface of the positive electrode active coating, drying to obtain the second separator coating 4, and preparing the positive electrode sheet for the sodium ion battery.
[0042] Add carboxyvinyl chloride to the solvent and stir to obtain carboxyvinyl chloride slurry; then add lithium hydroxide to the solvent and stir to obtain lithium hydroxide solution, seal the lithium hydroxide solution and store it for later use, add boehmite and conductive agent to the carboxyvinyl chloride slurry and stir to obtain a mixture, then slowly add lithium hydroxide solution and an appropriate amount of solvent, adjust the viscosity, and stir to obtain a separation coating slurry. Add the obtained separation coating slurry to the coating transfer tank, apply it to the surface of the aluminum foil and the surface of the active material coating by an extrusion coating machine, and bake it in an oven to obtain the separation coating.
[0043] In some embodiments, the vacuum degree of the vacuum stirring in step S3 is ≤-30KPa, the stirring speed is 10-30rpm / min, and the stirring time is 20-50 minutes. The vacuum degree of the secondary vacuum stirring is ≤-90KPa, the stirring speed is 10-30rpm / min, and the stirring time is 20-50 minutes. Preferably, the vacuum degree of the vacuum stirring is -10KPa, -15KPa, -20KPa, -25KPa, -30KPa, the stirring speed is 10rpm / min, 15rpm / min, 20rpm / min, 25rpm / min, 30rpm / min, the stirring time is 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, the vacuum degree of the secondary vacuum stirring is -60KPa, -65KPa, -70 KPa, -75KPa, -80KPa, -85KPa, -90KPa, the stirring speed is 10-20rpm / min, 20-30rpm / min, specifically, the stirring speed is 10rpm / min, 15rpm / min, 20rpm / min, 25rpm / min, 30rpm / min, and the stirring time is 20 minutes, 24 minutes, 26 minutes, 28 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes.
[0044] A sodium ion battery comprises the above-mentioned positive electrode sheet for sodium ion battery. Specifically, a sodium ion battery comprises a negative electrode sheet, a diaphragm, an electrolyte, a shell and the above-mentioned positive electrode sheet for sodium ion battery, wherein the diaphragm separates the positive electrode sheet from the negative electrode sheet, and the shell is used to install the positive electrode sheet, the negative electrode sheet, the diaphragm and the electrolyte.
[0045] negative electrode
[0046] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material. The negative electrode active material may be one or more of soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with sodium. Among them, the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector may be various materials in the art that are suitable for use as a negative electrode current collector for sodium ion batteries. For example, the negative electrode current collector may be, but is not limited to, metal foil, and more specifically, may be, but is not limited to, aluminum foil.
[0047] Electrolyte
[0048] The sodium ion battery also includes an electrolyte, and an organic solution containing an organic solvent, a sodium salt, and an additive is used as the organic electrolyte. The sodium salt includes at least one of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium bisfluorosulfonyl imide, sodium tetrafluoroborate, and sodium bisoxalatoborate. The organic solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, dihexyl carbonate, methyl propyl carbonate, and methyl ethyl carbonate.
[0049] The separator can be any material suitable for sodium ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0050] Preferably, the shell is a square aluminum shell, a steel shell or an aluminum-plastic film.
[0051] Example 1
[0052] The separator coating slurry comprises functional material carboxyvinyl chloride, functional material boehmite, neutralizing agent lithium hydroxide, conductive agent SP and deionized water, and the ratio is 55:20:20:5:98. First, 55g carboxyvinyl chloride and 40g deionized water are mixed in a double planetary stirring tank to prepare carboxyvinyl chloride slurry, and 20g lithium hydroxide and 40g deionized water are mixed in a double planetary stirring tank to prepare lithium hydroxide solution and sealed for storage. 20g functional material boehmite and 5g conductive agent SP are added to the carboxyvinyl chloride slurry and stirred at high speed for 3h. The vacuum degree of the stirring process is ≤-30KPa. After the stirring, the lithium hydroxide solution and 18g deionized water are slowly added, stirred slowly for 30min, stirred at high speed for 2h, and then stirred slowly at 15rpm / min for 30min and the vacuum is turned on. The separator coating slurry is obtained after the vacuum degree is ≤-90KPa. The prepared separation layer slurry is added to the coating transfer tank, and is coated on the surface of the aluminum foil by an extrusion coater and dried to obtain a first separation coating 2 with a thickness of 8 μm and a porosity of 50%. The positive electrode active slurry is coated on the first separation coating 2 and dried to obtain a positive electrode active coating 3. The separation coating slurry is coated on the surface of the positive electrode active coating 3 and dried to obtain a second separation coating 4 with a thickness of 3 μm and a porosity of 30%, thereby obtaining a positive electrode sheet for a sodium ion battery.
[0053] Example 2
[0054] The difference from Example 1 is that the first separation coating layer 2 includes the following raw materials in parts by weight: 60 g of carbopol, 20 parts of lithium hydroxide, 20 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water. The second separation coating layer 4 includes the following raw materials in parts by weight: 60 g of carbopol, 20 parts of lithium hydroxide, 20 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water.
[0055] The rest is the same as Example 1 and will not be described again here.
[0056] Example 3
[0057] The difference from Example 1 is that the first separation coating layer 2 includes the following raw materials in parts by weight: 50 g of carbopol, 20 parts of lithium hydroxide, 20 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water. The second separation coating layer 4 includes the following raw materials in parts by weight: 60 g of carbopol, 20 parts of lithium hydroxide, 20 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water.
[0058] The rest is the same as Example 1 and will not be described again here.
[0059] Example 4
[0060] The difference from Example 1 is that the first separation coating layer 2 includes the following raw materials in parts by weight: 50 g of carbopol, 15 parts of lithium hydroxide, 15 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water. The second separation coating layer 4 includes the following raw materials in parts by weight: 60 g of carbopol, 20 parts of lithium hydroxide, 20 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water.
[0061] The rest is the same as Example 1 and will not be described again here.
[0062] Example 5
[0063] The difference from Example 1 is that the first separation coating layer 2 includes the following raw materials in parts by weight: 50 g of carbopol, 30 parts of lithium hydroxide, 30 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water. The second separation coating layer 4 includes the following raw materials in parts by weight: 60 g of carbopol, 20 parts of lithium hydroxide, 20 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water.
[0064] The rest is the same as Example 1 and will not be described again here.
[0065] Example 6
[0066] The difference from Example 1 is that the thickness of the first separation coating 2 is 8 μm, and the porosity is 50%; the thickness of the second separation coating 4 is 8 μm, and the porosity is 30%.
[0067] The rest is the same as Example 1 and will not be described again here.
[0068] Example 7
[0069] The difference from Example 1 is that: the thickness of the first separation coating 2 is 8 μm, and the porosity is 60%; the thickness of the first separation coating 2 is 10 μm, and the porosity is 30%.
[0070] The rest is the same as Example 1 and will not be described again here.
[0071] Example 8
[0072] The difference from Example 1 is that: the thickness of the first separation coating 2 is 8 μm, and the porosity is 30%; the thickness of the first separation coating 2 is 2 μm, and the porosity is 50%.
[0073] The rest is the same as Example 1 and will not be described again here.
[0074] Example 9
[0075] The difference from Example 1 is that: the thickness of the first separation coating 2 is 5 μm, and the porosity is 40%; the thickness of the first separation coating 2 is 4 μm, and the porosity is 50%.
[0076] The rest is the same as Example 1 and will not be described again here.
[0077] Example 10
[0078] The difference from Example 1 is that: the thickness of the first separation coating 2 is 5 μm, and the porosity is 50%; the thickness of the first separation coating 2 is 6 μm, and the porosity is 40%.
[0079] The rest is the same as Example 1 and will not be described again here.
[0080] Comparative Example 1
[0081] The difference from Example 1 is that there is no second separation coating 4 .
[0082] The rest is the same as Example 1 and will not be described again here.
[0083] Comparative Example 2
[0084] The difference from Example 1 is that there is no first separation coating 2 .
[0085] The rest is the same as Example 1 and will not be described again here.
[0086] Comparative Example 3
[0087] The difference from Example 1 is that there is no first separation coating 2 and no second separation coating 4 .
[0088] The rest is the same as Example 1 and will not be described again here.
[0089] Performance test: Sodium ion batteries prepared in the above Examples 1-10 and Comparative Example 1 were subjected to internal resistance test and capacity retention rate test. The test results are recorded in Table 1.
[0090] Capacity retention rate test: At 25°C, the sodium ion battery is charged to 4.0V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage of 4.0V, left to stand for 5 minutes, and then discharged to 1.5V at a constant current of 0.5C. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The sodium ion battery is subjected to 500 cycles of charge and discharge tests according to the above method, and the discharge capacity of each cycle is recorded. Cycle capacity retention rate (%) = discharge capacity of the 500th cycle / discharge capacity of the first cycle × 100%.
[0091] Table 1
[0092]
[0093] It can be seen from Table 1 that the sodium ion battery prepared in the present invention has lower internal resistance and higher capacity retention rate than the secondary batteries of Comparative Examples 1-3, with the internal resistance as low as 27.63 mΩ and the capacity retention rate as high as 99%.
[0094] By comparing Examples 1-5, it can be concluded that when the first separation coating 2 and the second separation coating 4 are provided to include the following raw materials in parts by weight: 50g of carboxyvinyl chloride, 20 parts of lithium hydroxide, 20 parts of boehmite, 5 parts of conductive agent and 98 parts of deionized water, the secondary battery prepared has better performance. The first separation coating 2 can separate the positive electrode current collector 1 and the positive electrode active coating 3, and the second separation coating 4 can separate the positive electrode active coating 3 and the outside air, thereby better protecting the positive electrode sheet, wherein carboxyvinyl chloride can effectively increase the porosity of the separation coating, thereby facilitating the adsorption of the electrolyte and the transmission of ions, the addition of boehmite can effectively inhibit the reaction between aluminum foil and sodium hydroxide, and at the same time can inhibit the reaction between sodium hydroxide in the active material and carbon dioxide and water in the air, in addition, boehmite is an excellent flame retardant, which can improve the safety performance of its battery core, and the addition of the conductive agent can effectively reduce the resistance value of the battery core and improve the electrical performance of its battery core.
[0095] By comparing Examples 1, 6-10, it can be concluded that when the thickness of the first separator coating 2 is set to 8μm and the porosity is 50%; the thickness of the second separator coating 4 is set to 3μm and the porosity is 30%, the prepared sodium ion battery has better performance. Because the thickness of the first separator coating 2 is too thick, it is easy to affect the sodium ion deintercalation between the positive electrode active coating 3 and the positive electrode current collector 1, the thickness of the first separator coating 2 is too thin, it is easy to be loosely bonded, the thickness of the second separator coating 4 is too thick, it is easy to affect the energy density, and the thickness of the second separator coating 4 is too thin, it is easy to be loosely bonded.
[0096] By comparing Example 1 and Comparative Examples 1-3, it can be concluded that the separator coating of the present invention is added with a conductive agent, which can reduce the internal resistance of the electrode, and the effect of the first separator coating 2 on reducing the internal resistance of the electrode is similar to that of the second separator coating 4 on reducing the internal resistance of the electrode, and the separator coating can improve the electrochemical performance of the electrode and improve the capacity retention rate.
[0097] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A positive electrode sheet for a sodium ion battery, characterized in that: It comprises a positive electrode current collector, a positive electrode active coating, a first separation coating arranged between the positive electrode current collector and the positive electrode active coating, and a second separation coating arranged on the outermost side of the positive electrode active coating, wherein the positive electrode current collector is an aluminum foil; The first separation coating layer comprises the following raw materials in parts by weight: 50 to 80 parts of carboxyvinyl poly, 10 to 30 parts of lithium hydroxide, 10 to 30 parts of boehmite and 2 to 10 parts of a conductive agent; The second separation coating layer comprises the following raw materials in parts by weight: 50 to 80 parts of carboxyvinyl poly, 10 to 30 parts of lithium hydroxide, 10 to 30 parts of boehmite and 2 to 10 parts of a conductive agent.
2. The positive electrode sheet for sodium ion battery according to claim 1, characterized in that: The porosity of the first separation coating is 30% to 60%.
3. The positive electrode sheet for sodium ion battery according to claim 1 or 2, characterized in that: The thickness of the first separation coating layer is 0.2-10 μm.
4. The positive electrode sheet for sodium ion battery according to claim 3, characterized in that: The porosity of the second separation coating is 30% to 60%.
5. The positive electrode sheet for sodium ion battery according to claim 1 or 4, characterized in that: The thickness of the second separation coating layer is 0.2-10 μm.
6. The method for preparing a positive electrode sheet for a sodium ion battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, adding carboxyvinyl polyol into a solvent and stirring to obtain carboxyvinyl polyol slurry; Step S2, adding lithium hydroxide to a solvent, stirring, and sealing to obtain a lithium hydroxide solution; Step S3, adding boehmite and a conductive agent to the carboxyvinyl polyslurry and stirring in vacuum, adding lithium hydroxide solution and a solvent, and stirring in vacuum for a second time to obtain a separator coating slurry; Step S4, coating the separator coating slurry on the surface of the aluminum foil, drying to obtain a first separator coating, coating the positive electrode active slurry on the surface of the first separator coating, drying to obtain a positive electrode active coating, coating the separator coating slurry on the surface of the positive electrode active coating, drying to obtain a second separator coating, and preparing a positive electrode sheet for a sodium ion battery.
7. A method for preparing a positive electrode sheet for a sodium ion battery according to claim 6, characterized in that: The vacuum degree of the vacuum stirring in step S3 is ≤-30KPa, the stirring speed is 10-30rpm, and the stirring time is 20-50 minutes. The vacuum degree of the secondary vacuum stirring is ≤-90KPa, the stirring speed is 10-30rpm, and the stirring time is 20-50 minutes.
8. A sodium ion battery, characterized in that: A positive electrode sheet for a sodium ion battery comprising any one of claims 1 to 7.
Citation Information
Patent Citations
Multilayer positive plate with lithium / sodium supplementing function, battery and preparation method
CN111834622A